An innovative green multi-generation system centering around concentrating PVTs and biomass heaters, design and multi-objective optimization. (15th March 2022) - Sadi, Meisam; Behzadi, Amir mohammad; Alsagri, Ali Sulaiman; Chakravarty, Krishna Hara; Arabkoohsar, Ahmad
Abstract: This article introduces an innovative off-grid biomass/solar-based building cooling/power system equipped with concentrated photovoltaic thermal (CPVT) panels, a specific biomass heater design, an absorption chiller, and thermal energy storage tanks. The hourly variation of performance, economic, and environmental metrics is evaluated to investigate the proposed system's feasibility for a case study building in India. The effect of significant operational parameters on the system's performance is assessed by observing their influence on levelized cost of energy, biomass effectiveness, solar and biomass heat load ratios, and levelized carbon dioxide emission. The optimum design and operating conditions are ascertained through a genetic algorithm-based multi-objective optimization approach contemplating techno-economic-environmental facets to be satisfied simultaneously. According to the results, the highest monthly heat and electricity produced by the CPVT system are 521.8 kWh and 593.4 kWh in May. The results further reveal that sugarcane baggas is an excellent option compared to the most commonly used biomass in India because of the lowest price sensitivity. The parametric study results show that increasing the generator temperature leads to a favorable techno-environmental condition. Besides, the results reveal that the increase in solar panels is not economically suitable due to a higher levelized cost of energy. The optimization outcomes demonstrate that the optimum values of levelized cost of energy, biomass effectiveness, and levelized carbon dioxide emission are 58.1 USD/MWh, 3342.3 MWh, and 233.6 kg/MWh, respectively. Eventually, it can be observed that the chiller size and mass flow rate entering the CPVT panels are sensitive parameters and the optimum range of the generator temperature is between 91 °C and 95 °C. Graphical abstract: Image 1 Highlights: A hybrid CPVT panel integrated with a specific biomass heater design for cooling and power generation is introduced. Techno-economic and environmental metrics are evaluated for a case study building in India. An advanced genetic algorithm optimization approach is applied to find the optimum design parameters and objectives. While chiller size is not a sensitive variable, increasing the generator temperature is techno-environmentally favorable. The optimum LCOE, CO2 emission, and biomass effectiveness are 58.1 USD/MWh, 3342.3 MWh, and 233.6 kg/MWh.